2019
DOI: 10.2399/prn.19.0272001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of distress experienced during pregnancy on prenatal attachment

Abstract: Gebelikte distres durumunun prenatal ba¤lanmaya etkisi Amaç: Gebelikte yaflanan distres durumunun prenatal ba¤lanmaya etkisini belirlemektir. Yöntem: Tan›mlay›c› ve kesitsel türde gerçeklefltirilen çal›flma, Mart-Temmuz 2018 aras›nda bir Vak›f Üniversitesi T›p Fakültesi Hastanesi Kad›n Hastal›klar› ve Do¤um Poliklini¤ine baflvuran 370 gebe ile gerçeklefltirildi. Veriler, tan›t›c› bilgi formu, prenatal ba¤lanma ölçe¤i ve prenatal distres ölçe¤i kullan›larak elde edildi. Verilerin analizinde, frekans ve yüzde da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 3 publications
(10 reference statements)
5
10
1
2
Order By: Relevance
“…This study showed that the prenatal attachment levels of the pregnant women was mediocre (61.57±11.73). Previous studies result also were similar with this study (Coşkun et al, 2019;Bakır and Sarızayim, 2020). A review of the literature showed that a higher prenatal attachment level is related to positive pregnancy, labor, and postpartum results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study showed that the prenatal attachment levels of the pregnant women was mediocre (61.57±11.73). Previous studies result also were similar with this study (Coşkun et al, 2019;Bakır and Sarızayim, 2020). A review of the literature showed that a higher prenatal attachment level is related to positive pregnancy, labor, and postpartum results.…”
Section: Discussionsupporting
confidence: 91%
“…So, planned pregnancies can increase the prenatal attachment level. Previous studies also support this finding (Ossa et al, 2012;Karakoç and Ozkan, 2017;Pakseresht et al, 2018;Coşkun et al, 2019;Karabulutlu et al, 2020;Çelik and Güneri, 2020). Pregnant women with unplanned pregnancies fall behind in receiving health care services, encounter more risky situations, have more complications, and have less self-care (Boden et al, 2015;Goossens et al, 2016;Srewart et al, 2016;Canella et al, In this regards, Zibellina et al highlighted that a planned pregnancy and women's level of education has great importance for the increase of prenatal attachment and a healthy pregnancy.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, it was found that the levels of worry about pain and distress likely to be experienced during labor affected the participants’ prenatal attachment levels. In studies in Turkey and the rest of the world, it has been discovered that pregnant women who had high levels of anxiety also had a lower quality of prenatal attachment (Coşkun et al, 2019; Pisoni et al, 2014; Wahyuntari & Puspitasari, 2021). Besides, Wilson and Simpson (2016) reported a positive relationship between anxiety about attachment and pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…An ad hoc power analysis was performed to estimate the appropriate sample size. In the literature review, it was determined that for the primary outcome of the study, the mean distress score in pregnancy, was previously reported as 62.35 (standard deviation 11.28) [ 22 ]. Accordingly, assuming that the mean post-intervention distress score would decrease by seven points in the study, the minimum required samples size was calculated as 42 pregnant women in each group, with a 5% margin of error and a two-tailed significance level, in a 95% confidence interval, and an 80% power to represent the population (42 pregnant women for the experimental group and 42 pregnant women for the control group).…”
Section: Methodsmentioning
confidence: 99%